Industrial Technology, 4.0 Based Robotic Arm - Sumedh Dilip Dhangar; Dipti Vikas More; Dakshak Haresh Patil; Mundhe Bhalchandra (International Journal of Recent Advances in Engineering and Technology, 2025)
The emergence of Industry 4.0 has revolutionized manufacturing by integrating advanced technologies such as the Internet of Things (IoT), artificial intelligence (AI), and big data analytics. This project focuses on developing an Industry 4.0-based robotic arm designed to enhance flexibility, efficiency, and precision in industrial operations. Unlike traditional robotic systems limited to fixed tasks, this robotic arm leverages real-time data processing and adaptive algorithms to dynamically respond to production environments. By utilizing IoT connectivity, it can seamlessly communicate with other machines, ensuring smart factory integration. Additionally, AI-driven predictive maintenance enhances decision-making capabilities, minimizing downtime and optimizing performance. This innovative approach addresses challenges related to customization, scalability, and automation in modern manufacturing, paving the way for a more intelligent and responsive industrial landscape.